At Tathbiqat Al Ushuliyyah Min Surah Al Baqarah Fi Dhaw` Tafsir As Sa'diy Dirasah Tahliliyyah - Kamaluddin, Kamaluddin (2016)
Thesis with the title: "Ushul Fiqh Application Toward The Chapter of Al-Baqarah based on As Sa'dy" is written by Kamaluddin for Master Degree in Syari'ah Islamiyyah, in Islamic Law Program. It has been known that Al Qur`anul Karim is the most important Syar'i statement which any general rule/guidance can be derived from this book in order to summarize law. Every Learner will not get any benefit in their study if they do not study or they do not pay attention toward the translation of verses in Al Qur'an, especially translation that focuses on Ushul Fiqh dimension. The benefit are including several examples of Ushul Fiqh which are easy to be used in practice. The ignorance toward ushul fiqh dimension will be a barrier for learners to understand ushul fiqh rule/regulation which is concluded from Al-Qur'an verses, in addition, this lack of attention will also hinder the lerners to understand the practical use of this ushul fiqh rule/regulation.As Syaikh 'Abdur Rahman As Sa'dy - may Allah Subhanawataala bless him - is one of scholars ('Ulama`) among other scholars who focuses on practical Ushul Fiqh's rule/regulation from Al Quran, Where he mentions many rules / regulations in the chapter of albaqarah, therefore the author makes it as the title of this study. The aim of this study are: To understand ushul fiqh rule/regulation which is written by A Sa'dy - may Allah Subhanawataala bless him - in his translation toward Al Baqarah. To understand the practical use of As Sa'dy Ushul Fiqh - may Allah Subhanawataala bless him - through his translation toward Al Baqarah. To prove practical appropriateness of As Sa'dy Ushul Fiqh - may Allah Subhanawataala bless him - through his Ushul Fiqh theory which can be found in his book: Ar Risalah Al Lathifah and Al Qawa'id Al Hisan. The design of this study is deductive analysis explanatory, using logical approach. The result of this study as follows: As Sa'dy - may Allah Subhanawataala bless him - his translation of Al The Chapter of Baqarah has discussed the majority of Ushul Fiqh issues, which is around fifty Ushul Fiqh rules/regulations. He - may Allah Subhanawataala bless him - has already linked Ushul Fiqh rule/regulation with examples from Al Qur'an, which can provide benefit toward learners and scholars in order to provide more practical examples for clearer explanation. Ushul Fiqh practice of As Sa'dy - may Allah Subhanawataala bless him - also well-matched with his Ushul Fiqh theory in his book called: ArRisalah Al Lathifah and Al Qawa'id Al Hisan. Key word: Ushul Fiqh Application, The Chapter Al Baqarah, Translation of As Sa'dy.